Analytical Techniques for a Numerical Solution of the Linear Volterra Integral Equation of the Second Kind. (23rd November 2009) - Berenguer, M. I.; Gámez, D.; Garralda-Guillem, A. I.; Ruiz Galán, M.; Serrano Pérez, M. C.
Abstract : In this work we use analytical tools—Schauder bases and Geometric Series theorem—in order to develop a new method for the numerical resolution of the linear Volterra integral equation of the second kind.